DEVELOPING AUDIENCE SKILLS IN USING DIGITAL TECHNOLOGIES (Academicia Globe: Inderscience Research, 2023)
This article discusses the issue of assessing the level of digital literacy in the development of listeners skills in the use of digital technologies in the process of professional development.